Western imperialism in the Middle East 1914-1958 - Fieldhouse, D. K. (David Kenneth), 1925-2018 (OUP E-Books., 2006)
The Middle East is constantly in the news and is a major focus for international conflict. This book attempts to explain why this is so. It covers the crucial period after 1914, when the Ottoman empire was defeated and its provinces taken over by Britain and France, ending in 1958, when the Iraqi revolution finally ended British influence in the region. It describes both British and French policies and the reactions of Arabs and Jews. - ;The term 'Fertile Crescent' is commonly used as shorthand for the group of territories extending around the Rivers Tigris and Euphrates. Here it is assumed to.